IMPLEMENTATION OF PROTECTION FOR CHILD VICTIMS IN THE CRIMINAL JUSTICE PROCESS - Gina Salsabila Putri; Harits Tirta Rofif; Abid Nur Fariz Pamungkas; Nadhila Shiba Afisa; Waluyadi Waluyadi (Ann Publisher, 2025)
Abstract: Background. Aims. The purpose of this study is to evaluate the effectiveness of legal protection provided to child victims of abuse in the criminal justice process. This study uses a Normative Juridical approach. Methods. Secondary and primary data were used to sharpen the analysis. The data collection technique was library research for secondary data and observation for primary data. Meanwhile, the data was analyzed qualitatively. Result. The study's results show that children have the right to special protection and access to opportunities guaranteed by law for their physical, mental, and social growth and development. Conclusion. Children are protected in all aspects of life, including juvenile criminal justice, as Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA) regulates the protection of children who are victims of criminal acts. Implementation. To prevent child abuse, a comprehensive strategy and cooperation between stakeholders are needed, such as increasing the need for children's social interaction and strengthening the communication bond between parents and children.